Inflation, trade frictions, and productive activity in a multiple-matching model of money - Derek Laing; Victor E. Li; Ping Wang (Federal Reserve Bank of Atlanta, 2000)
This paper investigates the relationship between money growth, inflation, and productive activity in a general equilibrium model of search. The use of a multiple-matching technique, where trade frictions are captured by limited consumption variety, allows us to study price determination in a search-theoretic environment with divisible money and goods. In our basic framework, productive activity and matching in the goods market are endogenized by a time allocation decision of work and shopping effort. We find that in such an environment, a positive feedback between shopping and work effort decisions creates a channel by which inflation can positively influence productive activity. This feature also creates the possibility of multiple steady state equilibria when household preferences for variety is sufficiently great. We also consider an alternative means of endogenizing the matching technology through endogenous firm entry. Consistent with the findings of our basic framework, the importance of search frictions continues to be essential for the non-uniqueness of equilibria and an additional channel which links money growth to real activity.
Keywords: 330; Inflation (Finance); Prices; Production (Economic theory)